Effect of Fermentation on Physical and Chemical Characteristics, Bioactive Compounds, and Antioxidant Activity in Bitter Bean and Bamboo Shoot - Maicaurkaew, Sukanya; Apirattananusorn, Supaporn; Lueamsaisuk, Chalida; Junlakan, Wannapit; Sribuathong, Supannikar (Recent Science and Technology, 2025)
Fermentation is a folk wisdom used to extend the shelf life of food and make it taste better. In addition, fermentation produces probiotic bacteria that are beneficial to the body. This research aims to study the effects of fermentation on the physical and chemical characteristics, bioactive compounds, and antioxidant activity in bitter bean(Parkia speciosa) and bamboo shoots (Dendrocalamus asper). Bitter bean and bamboo shoots were fermented under controlled laboratory conditions using a brine solution consisting of 3 % salt and 40 % rice wash. The solution was brought to a boil and allowed to cool before being poured over the prepared samples in sterile containers. The fermentation process was carried out over a period of 14 days with the containers sealed. Bitter bean and bamboo shoots were femented in a laboratory setting and compared with market-sourced fermented bitter bean and bamboo shoots, as well as fresh bitter bean and bamboo shoots. The results showed that that fermentation led to decreased lightness (L*) and yellowness (b*), but increased redness (a*). Additionally, fermentation reduced pH while increasing ash and acid content compared to fresh bamboo shoots (p < 0.05). Furthermore, fermentation significantly boosted antioxidant activity, total phenolic content, total tannins, GABA, and beta-carotene levels (p < 0.05). However, it caused a significant reduction in vitamin C, chlorophyll A, B, and total chlorophyll levels (p < 0.05). In summary, fermenting bitter bean and bamboo shoots affected the physical and chemical characteristics, as well as the bioactive compound and antioxidant activity properties.